From Pathway to Destination: A Preliminary Investigation into the Transition of Pathway Students to Undergraduate Study - Dunworth, Katie; Fiocco, M.; Mulligan, D. (Australian Council for Private Education and Training (ACPET), 2012)
This article describes the results of a study conducted into the transition of students from a diploma course into mainstream university undergraduate programs. The main aim of the study was to explore the issues that relate to successful transition from the perspective of the students themselves. To that end, data were collected from 78 respondents to an online survey of students enrolled in mainstream study in a public university, who had previously undertaken a diploma with the private pathway provider. Follow-up in depth interviews were conducted with 10 students. Issues that were considered included English language development, academic adjustment and social adjustment Participants were also invited to comment on their experience of the pathway provider in terms of how well it prepared them for mainstream study. The findings indicated that there are many factors which can facilitate successful transition, and that in general the pathway was valued for its capacity to ease students into becoming familiar with the university environment and coping with the demands of mainstream study.